Non-Fungible Tokens: A Literature Review - Hokianto, Hugo Fostin (CV. Media Digital Publikasi Indonesia, 2023)
Non-Fungible Tokens (NFTs) was a popular crypto asset in the year 2021-2022, where viral news involving a NFT with huge price being sold causes a big interest to NFTs and OpenSea, one of the biggest NFT market place, and creating supply and demand for buying and selling NFTs, especially people who are only aware of cryptocurrency becoming the one who buys cryptocurrency and crypto assets. Although NFTs has since lost its initial exposure, the literatures of NFTs remains scarce, and the research involving NFTs has since been lower. This research is aimed to reviews literatures involving NFTs, using literature review method with „NFTs“ or „Non-Fungible Tokens“ as keywords to search for relevant literatures and research articles. The result of the research gave a definitive definition of NFTs compiled from many authors, the method people use to create NFTs and ways to invest NFTs safely, opportunities and risks in investing NFTs and the technological aspect, and what the future has for NFTs, investing and technological wise.